Constitutional Complaint Sebagai Penambah Kewenangan Baru Dalam Undang-Undang Mahkamah Konstitusi Republik Indonesia - Nurul Komariah; Muhammad Romadhoni Nur Matori Ridwan; Alivia Vabesta; Ginanjar Damayanti; Siti Nariyah (STAATSRECHT: Indonesian Constitutional Law Journal, 2020)
Guarantee the rights of every citizen for violations of constitutional rights by seeking to increase the authority of the Judicial Review Request by every justice seeker for violations of constitutional rights, but not at least the petition was granted.  The Mahkarnah of the Constitution, which checks what the petition is made of, often considers that what the Judicial Review proposes is not the subject of acknowledgment.  Constitutional Court Judges considered it to be a Constitutional complaint in which this constitutional complaint was not part of the Court's authority in accordance with the Constitution of the Republic of Indonesia and the applicable Law on the Understanding of the Constitution.  As a legislative body, the DPR is the one who has the right to change the Constitutional Court Law by including the authority of Constitutional complaint to the Constitutional Court. In this paper the author uses a research method in the form of quality data analysis with secondary sources of literature and deductive logic analysis.  Consitional Complaint to the Constitutional Court.